Inflammatory, oxidative and DNA damage status in vegetarians: is the future of human diet green? - Gajski, Goran; Gerić, Marko; Jakaša, Ivone; Peremin, Ines; Domijan, Ana-Marija; Vučić Lovrenčić, Marijana; Kežić, Sanja; Bituh, Martina; Moraes de Andrade, Vanessa (Critical reviews in food science and nutrition, 2023)
The health benefit of a vegetarian diet is still under debate as it may result in a higher intake of some beneficial micronutrients, while others may be reduced, thus influencing various metabolic pathways and health-related biomarkers. This scoping review discusses inflammatory, oxidative and DNA damage status in vegetarians and vegans compared to omnivores. Most of the reviewed studies indicated favorable effects of a vegetarian diet on oxidative status compared to omnivores but did not clearly associate particular dietary habits to genome damage. The evidence on the effect of vegetarian diet on the inflammatory and immunological biomarkers is poor, which could at least partly be explained by methodological constraints such as small sample size, short duration of vegetarianism and inconsistent definitions of the omnivorous diet. The only inflammatory biomarker that seems to be associated with the vegetarian diet was inflammatory mediator C-reactive protein, which in several studies showed lower values in vegetarians as compared to omnivores. There were very few studies on immunological markers and the results on the difference between vegetarians and omnivores were inconclusive. Although several biomarkers involved in oxidative stress and inflammation showed a beneficial association with the vegetarian diet, further research in well-defined and sufficiently sized cohorts is needed to provide more evidence.